2004
DOI: 10.1186/1478-4491-2-14
|View full text |Cite
|
Sign up to set email alerts
|

Dual practice in the health sector: review of the evidence

Abstract: This paper reports on income generation practices among civil servants in the health sector, with a particular emphasis on dual practice. It first approaches the subject of public–private overlap. Thereafter it focuses on coping strategies in general and then on dual practice in particular.To compensate for unrealistically low salaries, health workers rely on individual coping strategies. Many clinicians combine salaried, public-sector clinical work with a fee-for-service private clientele. This dual practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
247
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(265 citation statements)
references
References 55 publications
8
247
1
4
Order By: Relevance
“…7 Dual practice is emerging as an important challenge to health policy makers in developing countries because it may have direct implications for health workers' labor supply, and for the quantity and quality of care provided. 5,8,9 Its opponents argue that it induces undesirable behavior in health workers, such as supplier-induced demand and cream skimming. 10 Increased absenteeism of physicians from public hospitals to focus their time and attention in private practice, from which they generate more income, is featured widely in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Dual practice is emerging as an important challenge to health policy makers in developing countries because it may have direct implications for health workers' labor supply, and for the quantity and quality of care provided. 5,8,9 Its opponents argue that it induces undesirable behavior in health workers, such as supplier-induced demand and cream skimming. 10 Increased absenteeism of physicians from public hospitals to focus their time and attention in private practice, from which they generate more income, is featured widely in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…10 Increased absenteeism of physicians from public hospitals to focus their time and attention in private practice, from which they generate more income, is featured widely in the literature. 5 Other cited unethical behaviors to promote private practice at the cost of public services include physicians giving their best performance at their private practice while keeping a minimal level of effort at the public hospitals, 8 referring public facility patients to their private practice, and intentionally altering the quality of treatment, increasing waiting times, and reducing communication with patients in the public hospitals to divert patients to their private practice. Without mechanisms to control such behavior, the cost of dual practice can surpass the benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such high levels of statement disagreement raise the concern that a social desirability bias may have been operating here. The high agreement mean score on the Commitment to work dimension was also surprising as it has been previously reported that health workers in Mozambique combine their salaried work in the public sector with clinical practice with a fee-for-service private clientele [47,48]. …”
Section: Discussionmentioning
confidence: 99%
“…In order to compensate, many have been forced to pick and choose patients who come to the public health service and transfer the most profitable ones to their private clinics. [28][29][30] Such actions have reinforced the privatisation of health care, while paradoxically securing the existence of public services, which benefit from the political support of doctors' professional associations.…”
mentioning
confidence: 99%